2021
DOI: 10.1093/ecco-jcc/jjab076.723
|View full text |Cite
|
Sign up to set email alerts
|

P602 Vedolizumab subcutaneous influencing disease course in Constant-care app solution

Abstract: Background The Constant-care app solution (CC) has been shown to empower patients with mild-moderate Ulcerative Colitis (UC) in 5-ASA treatment and improve disease specific quality of life (1). Here we present preliminary data on our study to investigate the effects of CC on quality of life in patients with moderate-severe UC or Crohns Disease (CD) treated with s.c.vedolizumab, launched in June 2020 in Denmark. Methods The st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…51 A relatively large number of trials on VDZ SC reported satisfactory outcomes. 34,[36][37][38][39][40][41][52][53][54][55][56][57][58][59][60] Therefore, we sought to systematically review studies on VDZ SC for treating patients with IBD and to meta-analyze studies with relatively complete outcomes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…51 A relatively large number of trials on VDZ SC reported satisfactory outcomes. 34,[36][37][38][39][40][41][52][53][54][55][56][57][58][59][60] Therefore, we sought to systematically review studies on VDZ SC for treating patients with IBD and to meta-analyze studies with relatively complete outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…Two other conference abstracts also showed that patients with IBD who switched from VDZ IV induction therapy to SC maintenance therapy could continue their previous clinical outcomes. Norgaard 53 observed that after conversion, 2 of 15 patients achieved complete clinical remission at 24 months of maintenance therapy.…”
Section: Discussionmentioning
confidence: 99%